Decomposition of NOx and PM emission in Diesel Exhaust by Electrochemical reactor with Multilayered Electrodes - Muthiya, S.Jenoris; Pachamuthu, Senthilkumar (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
NOx emissions are highly poisonous and reactive gas liberated excessively from diesel engines. This work attempts to decrease NOx emissions by developing electrochemical reactor. The electrochemical reactor consists of electrochemical cells placed inside it. The electrochemical cells are fabricated by YSZ as an electrolyte middle layer coated with NiO -YSZ as cathode layer and Ag-YSZ as anode layer. The electrochemical cells are tested with diesel exhaust in a single cylinder dieselengine. By passing the variable voltage to the electrochemical cell, it is observed that up to 70% NOx reduction and 65% PM reduction was achieved with electrochemical cell. Further by coating the BaO NOx storage material, NOx reduction was reduced to 75% and PM reduction up to 70% was achieved. NOx reduction was greater with electrochemical cell -2.The presence of NOx storage material causes more NOx decompositions in the cathode layers. NOx decomposition also increases the oxygen concentrations, which further oxidizes the HC and PM emissions.The increase in NO decomposition was due to the increase in the ionic conductivity of the YSZ substrate. NOx reduction by electrochemical cell is a cost effective method.